2020
DOI: 10.1002/vms3.316
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and its metabolites induce mitochondrial membrane depolarization and caspase‐3 activation in equine neutrophils

Abstract: Neutrophils participate in innate immunity as the first line of host defence against microorganisms. However, persistent neutrophil activity and delayed apoptosis can be harmful to surrounding tissues; this problem occurs in diverse inflammatory diseases, including asthma‐affected horses. Previous studies in horses with acute lung inflammation indicated that treatment with tamoxifen (TX), a selective oestrogen receptor modulator, produces a significant decrease in bronchoalveolar lavage fluid (BALF) neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Additionally, they indicate that the inhibition of membrane estrogen receptors (GPR30) was able to reverse TAM-induced autophagy, but not its effect on cell viability, speculating that these off-target mechanisms of TAM could be associated with its inhibitory effect on PCK or directly on the mitochondria. Something similar was described by our group on equine neutrophils since this drug is also capable of inducing a marked loss of mitochondrial membrane potential at similar concentrations, which was associated with caspase-3 activation and cell apoptosis ( 49 ). The same occurs in the case of PS translocation, demonstrating a significant increase in the case of neutrophils incubated with TAM at a concentration of 2 μM ( 21 ).…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, they indicate that the inhibition of membrane estrogen receptors (GPR30) was able to reverse TAM-induced autophagy, but not its effect on cell viability, speculating that these off-target mechanisms of TAM could be associated with its inhibitory effect on PCK or directly on the mitochondria. Something similar was described by our group on equine neutrophils since this drug is also capable of inducing a marked loss of mitochondrial membrane potential at similar concentrations, which was associated with caspase-3 activation and cell apoptosis ( 49 ). The same occurs in the case of PS translocation, demonstrating a significant increase in the case of neutrophils incubated with TAM at a concentration of 2 μM ( 21 ).…”
Section: Discussionsupporting
confidence: 70%
“…In particular, mitochondrial membrane potential (∆ ψ m ) depolarization appears to be an early mitochondrial event leading to cell death [ 60 ]. Correspondingly, many weak base drugs are known to depolarize the mitochondrial membrane potential [ 61 , 62 ] and our findings clearly showed that the weak base drug-induced efflux of Fe 2+ from endolysosomes caused mitochondrial depolarization as well as cell death.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the source of ROS that triggers NETs by TX should come from the mitochondria. Likewise, Albornoz et al (15) showed that tamoxifen, N-desmethyltamoxifen and endoxifen depolarize the mitochondrial membrane and activate caspase-3 in healthy equine neutrophils in vitro. These results suggest that TX has the capacity to produce alterations in mitochondria, probably by stimulating the release of mtROS.…”
Section: Discussionmentioning
confidence: 97%
“…Tamoxifen (TX), a selective estrogen receptor modulator which belongs to the triphenylethyllenes group of molecules, is used as a treatment in all stages of estrogen-positive human breast cancer. It has potent anti-inflammatory effects: we have described an early pro-apoptotic effect of tamoxifen in granulocytic cells, both in vitro with peripheral blood and BALF (13), and in vivo (14); in addition, we showed that tamoxifen and its metabolites can activate the intrinsic apoptotic pathway in equine neutrophils (15). Our laboratory group has also shown that tamoxifen has an inhibitory action on respiratory burst, chemotaxis and chemokinesis of equine neutrophils in a dose-dependent manner (16,17), and that tamoxifen induces efferocytosis by macrophages and modulates immune function through an estrogen-independent mechanism (18,19).…”
Section: Introductionmentioning
confidence: 88%